1985
DOI: 10.1080/00031305.1985.10479422
|View full text |Cite
|
Sign up to set email alerts
|

An Expanded Approach to Educating Statistical Consultants

Abstract: This article describes an expanded approach to the education of statistical consultants that is being implemented at Florida State University. Our program begins with a preconsulting course in which students first study general problem-solving techniques. Next these techniques are used in solving applied statistics "textbook" problems. Then problem formulation and research methods are studied. Finally the structure of consulting sessions is considered, along with interpersonal issues that arise in consulting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Zahn and Isenberg (1983) provided a reference on nonstatistical aspects of consulting, while Kirk (1991) discussed consulting in universities. On this same issue, McCulloch, Boroto, Meeter, Polland, and Zahn (1985) suggested using videotaping to evaluate both statistical and nonstatistical aspects of consulting. They also suggested that universities offer a supervised consulting course.…”
Section: Review Of Previous Suggestionsmentioning
confidence: 99%
“…Zahn and Isenberg (1983) provided a reference on nonstatistical aspects of consulting, while Kirk (1991) discussed consulting in universities. On this same issue, McCulloch, Boroto, Meeter, Polland, and Zahn (1985) suggested using videotaping to evaluate both statistical and nonstatistical aspects of consulting. They also suggested that universities offer a supervised consulting course.…”
Section: Review Of Previous Suggestionsmentioning
confidence: 99%
“…With random pairings to clients, the learning experience is not uniform for the students. McCulloch et al (1985) discuss this type of pedagogical approach with their students; after a semester-long preconsulting course, students then worked for two semesters in consulting courses where they worked with real-life clients and videotaped these interactions for feedback (McCulloch et al, 1985). This mimicked on-the-job training while also allowing for supervision of students and a real-time feedback component, allowing for a cycle of feedback and learning (McCulloch et al, 1985).…”
Section: Pedagogical Models For Statistical Consulting Curriculamentioning
confidence: 99%
“…Beyond analyzing data, producers assume the primary responsibility for communicating new statistical information to consumers which requires strong technical communication skills (Kirk, 1991;McCulloch, Boroto, Meeter, Polland, & Zahn, 1985). Producers interact with consumers who vary in statistical literacy, and assume additional responsibilities when working with individuals who exhibit limited numeracy (Kirk, 1991;Boland, 2003).…”
Section: Statistical Literacy Producers and Consumersmentioning
confidence: 99%